Validation of the technique aimed at the determination of FMD antibodies in liquid phase blocking sandwich Elisa - N. N. Lugovskaya; Ye. N. Kalinina; K. S. Maikova; O. V. Vorobyova; G. M. Goryacheva; T. K. Mayorova (Ветеринария сегодня)
The paper describes the process of the validation of the technique aimed at the determination of FMD antibodies in liquid phase blocking sandwich ELISA for FMD types A, 0 and Asial. The results were analyzed and the following main validation characteristics were determined: sensitivity, specificity, accuracy, consistency, predictability of positive and negative results, reproducibility and intermediate precision under the conditions of repeatability and reproducibility. The results of the ELISA procedure validation were in compliance with the acceptability criteria.